2014
DOI: 10.4236/aim.2014.411079
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of a Clinical Strain of <i>Mycoplasma fermentans</i> to Human Cultured Epithelial Cells

Abstract: This study compares the kinetics of adherence of both the prototype strain PG-18 and the recently clinically isolated strain P-140 of Mycoplasma fermentans to HEp-2 cells. M. fermentans may induce respiratory and genitourinary tract infections. We investigated the presence of putative adhesins from strain P-140. A surface protein of 47 kDa, labeled SP47, isolated from M. fermentans P-140, seems to be involved in acterial adherence on HEp-2 cells; this study could allow helping understand the interaction betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Interestingly, FP29 also has the capacity to block binding of M. hominis to HeLa cells which would suggest that these two organisms share a similar mechanism with regards to cell interaction [55]. Studies by Rosales-P erez et al [54] have also revealed the involvement of a putative 40 kDa protein (named as SP40 by the authors) in the adherence of M. fermentans P140 to cultured human epithelial cells (HEp-2). Anti-SP40 antibodies has been reported to prevent the clustering of M. fermentans P140 and its attachment to the HEp-2 cells as evidenced by enzyme immunoassay (EIA) technology.…”
Section: Virulence Factors In Hostmycoplasma Attachmentmentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, FP29 also has the capacity to block binding of M. hominis to HeLa cells which would suggest that these two organisms share a similar mechanism with regards to cell interaction [55]. Studies by Rosales-P erez et al [54] have also revealed the involvement of a putative 40 kDa protein (named as SP40 by the authors) in the adherence of M. fermentans P140 to cultured human epithelial cells (HEp-2). Anti-SP40 antibodies has been reported to prevent the clustering of M. fermentans P140 and its attachment to the HEp-2 cells as evidenced by enzyme immunoassay (EIA) technology.…”
Section: Virulence Factors In Hostmycoplasma Attachmentmentioning
confidence: 96%
“…cell-cell adhesion, signalling and differentiation) and pathological processes (e.g. metastasis) are reported to be associated with the presence of O-acetylated sialoglycoconjugates (O-AcSGs) in cell membranes [51,53,54].…”
Section: Virulence Factors In Hostmycoplasma Attachmentmentioning
confidence: 99%
See 1 more Smart Citation